The spatial and scalar implications of missions: Challenges and opportunities for policy - Elvira Uyarra; Iris Wanzenboeck; Kieron Flanagan (The University of Manchester, The Manchester Institute of Innovation Research (MIoIR), 2023)
In recent years, debates about innovation policy have highlighted a broader scope for action and a widening of the range of policy goals such policies are expected to (or might be expected to) address. Scholars and analysts have both detected but also advocated a shift from generic and primarily R&D-based innovation support measures towards a new (or third) 'generation' of innovation policy - variously referred to as challenge-led, mission-orientated or transformative innovation policies. This new generation of innovation policy thinking is a response to major societal challenges such as climate change, migration, or food and energy security - the implication being that traditional innovation policies were either inadequate in response to or else uninterested in such challenges. A more targeted and challenge-oriented innovation policy should, it is argued, help to deliver desired, and not just more, innovations. This implies a more active role of the state in funding risk-taking activities and in creating - not just correcting - markets. This 'normative turn' in innovation policy has also been observed in the design and implementation of regional policies, with a greater emphasis on the socio-ecological dimension of innovation, particularly in the context of the European Green Deal and the Innovation Strategies for Sustainability (S4). Whilst there is much agreement that bolder, more customised and directional policies are needed to tackle the societal challenges of our time, there is less consensus about how such policies should be implemented in practice.
Keywords: 330; Transformative innovation policies; Mission-oriented approaches; Societal challenges; Spatial and scalar dimensions; Regional innovation